Debjani Ganguly. This Thing Called the World: The Contemporary Novel as Global Form. Duke UP, 2016. - Evan Torner (Studies in 20th & 21st Century Literature, 2019)
Review of Debjani Ganguly. This Thing Called the World: The Contemporary Novel as Global Form. Duke University Press, 2016. 300 pp.
Keywords: world literature; post-1989 novel